The Effects of ‘Fear of Missing Out’ (FOMO) in Flash Sale Business Models: Strategy or Manipulation? - Hakim, Andy; Farid, Ahmad Salman (www.bsi.ac.id, 2025)
Fear of Missing Out (FOMO) is a psychological phenomenon that has been widely adopted in flash sale business models to create a sense of urgency and social pressure. While this strategy can be effective in increasing sales, it also raises ethical concerns regarding consumer manipulation. This study examines whether FOMO-based flash sales serve as a legitimate marketing strategy or a psychological exploitation tool. A qualitative research approach was used, employing semi-structured interviews with consumers who frequently participate in flash sales, as well as expert interviews with digital marketing professionals. Thematic analysis was conducted to identify key patterns related to consumer behavior, emotional responses, and ethical considerations. Findings reveal that FOMO-driven flash sales increase impulse buying but also contribute to buyer’s remorse and anxiety. Consumers often experience psychological pressure due to scarcity cues, leading to purchasing decisions based on perceived urgency rather than necessity. Additionally, the study highlights a thin line between marketing strategy and consumer manipulation, particularly in cases where artificial scarcity or misleading promotions are used. The discussion emphasizes that while FOMO-based flash sales are highly effective in short-term revenue generation, they may harm long-term consumer trust if perceived as deceptive. Ethical concerns regarding stress-inducing marketing tactics call for greater transparency in digital marketing. Future research should explore quantitative measures of consumer spending behavior and cross-cultural perspectives on FOMO marketing.